1994
DOI: 10.1007/bf00686689
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of intrahepatic arterial infusion of 4?-epidoxorubicin with Lipiodol versus 4?-epidoxorubicin alone in the treatment of hepatocellular carcinoma

Abstract: We conducted a prospective randomized trial to evaluate the efficacy of Lipiodol in intrahepatic arterial infusion chemotherapy for patients with hepatocellular carcinoma (HCC). A total of 38 patients with unresectable HCCs and underlying cirrhosis were entered in this trial, and 36 of them were evaluable. Every 4 weeks, 17 patients received 70 mg of 4'-epidoxorubicin (epirubicin) alone (group A), whereas 19 patients received a Lipiodol emulsion containing the same dose of epirubicin (group B) through the hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 6 publications
1
36
0
Order By: Relevance
“…Therefore, further studies should be published to ensure a solid assessment, mainly in reference to therapies with acceptable response rates, such as internal radiation [54][55][56] or arterial chemotherapy. [44][45][46][47][48][49][50] In summary, the present systematic review provides consistent evidence that arterial chemoembolization may benefit a subset of patients with unresectable HCC and thus proposes this therapy as the standard intervention in these cases. The data are relevant for the decision-making process of these patients, who at present do not have any option for cure.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, further studies should be published to ensure a solid assessment, mainly in reference to therapies with acceptable response rates, such as internal radiation [54][55][56] or arterial chemotherapy. [44][45][46][47][48][49][50] In summary, the present systematic review provides consistent evidence that arterial chemoembolization may benefit a subset of patients with unresectable HCC and thus proposes this therapy as the standard intervention in these cases. The data are relevant for the decision-making process of these patients, who at present do not have any option for cure.…”
Section: Discussionsupporting
confidence: 63%
“…comparison studies of Tae and Tac have shown that Tae treatment is associated with a higher survival rate than Tac in unresectable hepatic carcinoma patients (20,6). on the other hand, in a randomized prospective trial conducted to evaluate the efficacy of epirubicin alone vesus lipiodol emulsion containing the same dose of epirubicin in intrahepatic arterial infusion chemotherapy for hepatic carcinoma patients, lipiodol emulsion with epirubicin was shown to be more effective than epirubicin alone (11). The results of studies on the treatment of locally advanced cervical cancer were consistent with those on hepatic carcinoma: the tumor reduction ratio was significantly higher for the combination of intra-arterial cisplatin and gelfoam compared to gelfoam used alone, and cisplatin combined with other anticancer agents infused via the arteries had similar efficacy (12).…”
Section: Discussionmentioning
confidence: 99%
“…randomized controlled trials have shown that Tace appears to be more effective than Tac in hepatocellular carcinoma and cervical cancer treatment (11,12). These studies reported the clinical effects of tumor reduction and the patient survival rate under Tace treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, Lipiodol is used in combination with chemolipiodolization and TACE as a carrier of a chemotherapeutic agent in order to enhance various effects, including tumor selectivity, as well as to maintain the drug concentration. It is known that by suspending Lipiodol and EPI (22) or CDDP (23) and then injecting the suspending agent into the artery, an efficacy higher than that of a single use of EPI or CDDP alone is achieved. Moreover, 131I-Lipiodol containing radioiodine demonstrated favorable effects against hepatocellular carcinoma with a response rate of 48% and a MST of 27 months (24).…”
Section: Chemolipiodolizationmentioning
confidence: 99%